2017
DOI: 10.1039/c7ra04061j
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite photodetectors prepared by flash evaporation printing

Abstract: A flash evaporation printing methodology based on CNT films has been employed to fabricate perovskite photodetectors with high quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This is a comparable value to the detectivity of 6.14 × 10 11 Jones for the device with the spin-coated film. These device performance parameters are comparable to the previously reported MAPbI 3 -based photodetectors 31 , 56 58 and commercial Si photodetectors (< 0.2 A/W) 47 , 59 . Figure 6 b displays repeated on/off operation of the photodetector with the flash evaporated MAPbI 3 film.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…This is a comparable value to the detectivity of 6.14 × 10 11 Jones for the device with the spin-coated film. These device performance parameters are comparable to the previously reported MAPbI 3 -based photodetectors 31 , 56 58 and commercial Si photodetectors (< 0.2 A/W) 47 , 59 . Figure 6 b displays repeated on/off operation of the photodetector with the flash evaporated MAPbI 3 film.…”
Section: Resultssupporting
confidence: 88%
“…In addition, the high purity of the flash evaporated film is indicated by the absence of diffraction peaks that correspond to PbI 2 (asterisk marks (12.6°)). Note that this is an interesting observation because many previous studies 31 , 38 , 40 , 41 have demonstrated that the addition of excess MAI was necessary to deposit pure MAPbI 3 films without PbI 2 impurities (detailed discussion could be found in the Supplementary Information Sect. 1).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations